Time trends in axilla management among early breast cancer patients: Persisting major variation in clinical practice across European centers. (2nd June 2016) - Gondos, Adam; Jansen, Lina; Heil, Jörg; Schneeweiss, Andreas; Voogd, Adri C.; Frisell, Jan; Fredriksson, Irma; Johansson, Ulla; Tvedskov, Tove Filtenborg; Jensen, Maj-Britt; Balslev, Eva; Hartmann-Johnsen, Olaf Johan; et al.
Abstract: Background We examined time trends in axilla management among patients with early breast cancer in European clinical settings. Material and methods EUROCANPlatform partners, including population-based and cancer center-specific registries, provided routinely available clinical cancer registry data for a comparative study of axillary management trends among patients with first non-metastatic breast cancer who were not selected for neoadjuvant therapy during the last decade. We used an additional short questionnaire to compare clinical care patterns in 2014. Results Patients treated in cancer centers were younger than population-based registry populations. Tumor size and lymph node status distributions varied little between settings or over time. In 2003, sentinel lymph node biopsy (SLNB) use varied between 26% and 81% for pT1 tumors, and between 2% and 68% for pT2 tumors. By 2010, SLNB use increased to 79–96% and 49–92% for pT1 and pT2 tumors, respectively. Axillary lymph node dissection (ALND) use for pT1 tumors decreased from between 75% and 27% in 2003 to 47% and 12% in 2010, and from between 90% and 55% to 79% and 19% for pT2 tumors, respectively. In 2014, important differences in axillary management existed for patients with micrometastases only, and for patients fulfilling the ACOSOG Z0011 criteria for omitting ALND. Conclusion This study demonstrates persisting differences in important aspects of axillary management throughout the recent decade. The results highlight the need for international comparative patterns of care studies in oncology, which may help to identify areas where further studies and consensus building may be necessary.